Progress and strength of response against non-communicable diseases in the US-affiliated Pacific Island jurisdictions, 2010-2021 - Durand, Andre Mark; Cash, Haley L; Durand, Zoe (Western Pacific Surveillance and Response, 2022)
Objective: To determine the effectiveness of the response to the 2010 declared regional noncommunicable diseases (NCDs) emergency in nine US-affiliated Pacific Island jurisdictions. Methods: Vital statistics and risk prevalence surveys were retrospectively reviewed using 14 standardized NCD risk, prevalence and death rate indicators to measure changes in health status over time. NCD risk and prevalence change scores were derived from subsets of these indicators, and NCD composite death rates were examined. An NCD strength-of-intervention score derived from a standardized regional monitoring tool provided measures for assessing responses aimed at curbing risk factors, prevalence and death rates. Associations between the strength-of-intervention score and changes in health status were examined. Results: Pairs of values were available for 97 of 126 individual comparisons for 14 core indicators in nine jurisdictions. The composite mean prevalence of all risk factors across the jurisdictions between baseline and follow-up (26.7% versus 24.3%, P=0.34) and the composite mean diabetes and hypertension prevalence (28.3% versus 28.2%, P=0.98) were unchanged, while NCD death rates increased (483.0 versus 521.9 per 100 000 per year, P<0.01). The composite strength-of-intervention score for the region was 37.2%. Higher strength-of-intervention scores were associated with improvements in health indicators. Discussion: Despite some improvements in selected NCD indicators at the jurisdiction level, there was no significant overall change in the prevalence of risk factors, diabetes and hypertension, and death rates have continued to increase since the NCD emergency declaration. However, the adoption of public sector NCD interventions was associated with improvements in health indicators.